‘I felt the world crash down on me’: Women’s experiences being denied legal abortion in Colombia - Teresa DePiñeres (Reproductive Health, 2017)
Abstract Background In 2006, Colombia’s constitutional court overturned a complete ban on abortion, liberalizing the procedure. Despite a relatively liberal new law, women still struggle to access safe and legal abortion services. We aimed to understand why women are denied services in Colombia, and what factors determine if and how they ultimately terminate pregnancies. Methods We recruited women denied abortion at a private facility in Bogota. Twenty-one participants completed an initial interview and eight completed a second longer interview. Two researchers documented themes and developed and applied a codebook to transcripts using ATLAS.ti. Results Participants faced barriers, such as lack of knowledge of service availability and delayed pregnancy recognition, leading to denial. Five out of eight participants ultimately received abortions in public hospitals, due to support from partners and a robust referral system; nevertheless, they received poor care. Those who continued pregnancies endured stigmatizing events and inaccurate medical counselling at referral facilities. Several women contemplated illegal abortion though were afraid to attempt it. Conclusion We propose the following recommendations: 1) increase awareness about availability and legality of abortion services to prevent delay and consequent denial; 2) provide counseling and referral upon denial; and 3) train providers in interpersonal quality abortion care.